Method of producing a dispersible nano graphene or graphene oxide - Ibrahim, Nor Azowa; Chieng, Buong Woei; Hussein, Mohd Zobir (2014)
A method of producing a dispersible nano graphene or graphene oxide platelet material,including the steps of preparing graphite oxide by oxidizing graphite by reaction with an oxidising agent to form a solution, terminating oxidation process to form a graphite oxide suspension mixture and washing the graphite oxide suspension mixture with an additive, repeatedly washing to remove Cl- ions from the graphite oxide suspension mixture to form a final product. Subsequently, drying the final product and exfoliating one or more layers of graphene from the final product to obtain a dry powder of a single layer graphene oxide, and grinding the formed single layer graphene oxide to a fine nano graphene material.